Pain as a determinant of outgoing dispatch to events for Basic and Specialist Medical Rescue Teams on the example of the city of one of the selected provinces in Poland - Paweł Musiał (Kazimierz Wielki University, 2020)
Pain is perceived by patients as a multi-stage component of feelings and ailments that have accompanied the individual since the dawn of time. Diagnostics of pain is a problem that is subject to constant analysis in order to eliminate the symptoms that repeatedly constitute the basis for qualifying them to take medical actions to relieve pain and ensure full psycho-physical comfort. Pain is repeatedly a component of the ongoing pathological process in the body.